2017
DOI: 10.1021/acscatal.7b00778
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Stability of Cu Clusters of Low Atomicity against Oxidation. Effect on the Catalytic Redox Process

Abstract: By a combination of theoretical modeling and XPS and SERS spectroscopic studies, it has been found that it is possible to stabilize metallic copper species under oxidizing reaction conditions by adjusting the atomicity of subnanometer copper clusters. Small Cu 5 clusters display low reactivity toward O 2 dissociation, being less susceptible to oxidation than larger Cu 8 or Cu 20 systems. However, in the presence of water this reactivity is strongly enhanced, leading to oxidized Cu 5 clusters. In that case, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
82
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(97 citation statements)
references
References 49 publications
(80 reference statements)
11
82
2
Order By: Relevance
“…Thus, for the gas phase clusters, we see that Cu 4 is less prone to oxidation than Cu 12 or Cu 20 . This finding is in excellent agreement with the trends reported very recently by Concepción et al, who found that in the gas phase, Cu 5 is less easily oxidized than Cu 8 or Cu 13 . Importantly, comparing the left panels in Figure with the right panels, we find that the presence of the support significantly impacts oxidizability.…”
Section: Resultssupporting
confidence: 93%
“…Thus, for the gas phase clusters, we see that Cu 4 is less prone to oxidation than Cu 12 or Cu 20 . This finding is in excellent agreement with the trends reported very recently by Concepción et al, who found that in the gas phase, Cu 5 is less easily oxidized than Cu 8 or Cu 13 . Importantly, comparing the left panels in Figure with the right panels, we find that the presence of the support significantly impacts oxidizability.…”
Section: Resultssupporting
confidence: 93%
“…As one illustrative example, a previous study of the O 2 photodesorption from a reduced TiO 2– x surface highlighted the high multiconfigurational character of the wavefunction for the O 2 –TiO 2– x interaction, with TiO 2– x having being modeled as a cluster in a doublet spin state. 15 , 16 The analysis of the open-shell Cu 5 cluster in this work extends these previous DFT studies 10 , 23 by considering the multireference nature of the O 2 –Cu 5 interaction. Similarities, but also qualitative differences will be discussed in the following sections.…”
Section: Introductionsupporting
confidence: 59%
“…Much more energy can be harvested from sunlight, and the coated titanium dioxide stores this energy temporarily in the form of charge pairs—electrons and holes—which is a perfect prerequisite for follow-up chemistry. Moreover, experimental measurements 10 have indicated a particularly high stability of Cu 5 clusters with respect to oxidation up to a temperature of 423 K. The experiment by Corma’s group 10 was realized for copper clusters, with and without water, considering N-doped graphene as the support in XPS spectroscopic measurements. Our previous work has shown that a Cu 5 cluster is minimally perturbed when supported on graphene due to the dispersion-dominated nature of the Cu 5 –graphene interaction.…”
Section: Introductionmentioning
confidence: 99%
“…As most of the atoms are at the surface of the structure, they rearrange themselves to minimize the number of dangling bonds and the surface energy, giving rise to unexpected structures. Because of these particularities, interesting and high catalytic activities often arise (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Hence, heterogeneous catalysis has the potential to undergo a renaissance and to make possible many previously inaccessible industrial processes.…”
Section: Introductionmentioning
confidence: 99%